Experience with Building Mesolithic Huts in the Stone Age Park Dithmarschen in 2014 - Werner Pfeifer (EXARC, 2015)
Two new huts in the Stone Age Park Dithmarschen in Albersdorf (Germany) were built in spring 2014 by the Experimental Archaeologist and Educator Werner Pfeifer with the support of some friends and with financial support from the Stone Age Park Dihmarschen and the EU co-financed project OpenArch.